Masked Alkyne Equivalents for the Synthesis of Mechanically Interlocked Polyynes. Issue 11 (21st January 2021) - Gawel, Przemyslaw; Woltering, Steffen L.; Xiong, Yaoyao; Christensen, Kirsten E.; Anderson, Harry L.
Abstract: Polyyne polyrotaxanes, encapsulated cyclocarbon catenanes and other fascinating mechanically interlocked carbon‐rich architectures should become accessible if masked alkyne equivalents (MAEs) can be developed that are large enough to prevent unthreading of a macrocycle, and that can be cleanly unmasked under mild conditions. Herein, we report the synthesis of a new bulky MAE based on t ‐butylbicyclo[4.3.1]decatriene. This MAE was used to synthesize a polyyne [2]rotaxane and a masked‐polyyne [3]rotaxane by Cadiot–Chodkiewicz coupling. Glaser cyclo‐oligomerization of the [2]rotaxane gave masked cyclocarbon catenanes. The unmasking behavior of the catenanes and rotaxanes was tested by photolysis at a range of UV wavelengths. Photochemical unmasking did not proceed cleanly enough to prepare extended encapsulated polyyne polyrotaxanes. We highlight the scope and challenges involved with this approach to interlocked carbon‐rich architectures. Abstract : Active‐metal‐template synthesis has been used to prepare a [2]rotaxane in which the whole dumbbell component is a masked C16 H2 polyyne. t ‐Butyl substituents make the photo‐labile terminal groups bulky enough to act as stoppers and prevent unthreading of the macrocycle. Rotaxanes of this type are promising intermediates in the synthesis of mechanically interlocked carbon‐rich architectures, such as cyclocarbon catenanes and carbyne polyrotaxanes.